Asssessing Public Private Partnership in Indonesia Tourism - Bhayu Rhama; Ferry Setiawan (Policy & Governance Review, 2020)
Several studies have shown significant development in Indonesia tourism; however, works of literature that focus on the extent of successful stakeholders’ participation in Indonesia tourism are hard to be found. This study aims to determine the success of public-private partnership (PPP) in the development of tourism in Indonesia and uses a descriptive qualitative methodology by conducting a literature study on previous studies related to tourism development in Indonesia, which adopted the concept of PPP in 2012. The research result shows that the PPP concept can be effectively carried out in tourist destination development programs and tourist infrastructure improvement programs. In addition, several targets must be set to achieve the success of public private partnership in the development of tourism in Indonesia, namely: 1) creating competitive tourism globally or nationally, 2) creating cooperative tourism focusing on the service and tourist destination infrastructure, 3) creating tourism that has unique characteristics based on its natural conditions so it has its own identity.